Technological schemes of acid treatments - Rybalko, Serhiy Oleksandrovych; Khomenko, Volodymyr Lvovych (My University, 2023)
Acid baths are the simplest acid treatments and are designed to clean the walls of the well and the bottom from the remnants of cement and clay crusts, corrosion products, resinous substances, paraffin, etc. Simple acid treatments are most often used to dissolve the contaminants introduced into the reservoir, as well as to increase the size of the pore channels by dissolving the carbonate rock.
Keywords: acid bath; carbonate rock; pore channel; поровий канал; карбонатна порода